Adherence to four healthy lifestyles and their influencing factors among residents aged 35 to 75 years in Fujian province: a longitudinal study - Ze YANG; Xin FANG; Yefa ZHANG; Wenling ZHONG; Tiehui CHEN; Jingyu CHEN; Yanrong YIN; Xiaoqing LI (Zhongguo gonggong weisheng)
ObjectiveTo understand the adherence to four healthy lifestyle habits among residents of Fujian province and their influencing factors, and to provide a reference for chronic disease prevention and control and health management strategies for the population. MethodsA descriptive analysis of adherence to four healthy lifestyle habits, including non-smoking, non-drinking or moderate drinking, adequate physical activity during leisure time, and a healthy diet, was conducted among 31 610 residents aged 35 – 75 years who participated in the Fujian Provincial Early Screening and Comprehensive Intervention Program for High-Risk Cardiovascular Disease from 2016 to 2022. The correlation between these lifestyle habits and socio-demographic characteristics such as sex, age, and education level was also explored. ResultsAfter age and sex standardization, the adherence rates to the four individual healthy lifestyle habits among the 31 610 residents in Fujian province, from the highest to the lowest, were non-drinking or moderate drinking (95.7%), non-smoking (76.2%), adequate physical activity during leisure time (26.1%), and a healthy diet (11.4%). Only 3.4% of the residents adhered to all four healthy lifestyle habits simultaneously. Multifactorial logistic regression analysis showed that women, older adults aged ≥ 65 years, non-farmers, and residents with higher education levels were more likely to adhere to all four healthy lifestyle habits. ConclusionsThe adherence to the four healthy lifestyle habits among residents of Fujian province has not reached an ideal state. Healthy lifestyle habits are associated with sex, age, and education level. There is an urgent need to formulate targeted health promotion strategies and implement comprehensive intervention measures.